HAMZA IMOMBERDIEV’S COLORFUL POETRY - Dilfuza Rasulmuxamedova (International Engineering Journal For Research & Development, 2021)
This article is dedicated to children’s poetry. The study and analysis of the works of the poet and multifaceted artist H.Imomberdiev, who has a specific status in children's literature, as well as the analysis of the author's poems unknown to many lovers of literatureare considered in this article. The poet’s works are distinguished by the fact that their essence being deep and broad in meaning, have a great educational significance